Desiccation-Tolerant Vascular Plants: A Group of Species Largely Neglected in Conservation - Wassila Ibrahim Seidou; Luiz Bondi; Stefan Porembski; Edson Lezin Bomisso (Plants, 2025)
The anthropogenic drivers of biodiversity loss are causing a global decline in biodiversity, yet some species remain overlooked in conservation efforts. In this study, we address the gaps between the current discussions and pressing issues on these species’ conservation. We focused on West Africa and used desiccation-tolerant vascular plants to conduct a systematic review of conservation discussions and a study case to assess their protection and exposure to quarrying and climate change. Our systematic review revealed, for the first time, that these plants are largely neglected in conservation discussions. Most species lack formal evaluations, and only four studies mentioned conservation, although without providing enough evidence to justify it. In our case study, we found biased protection among the species, with varying effectiveness of the protection areas against different anthropogenic threats. The two most exposed species were not present in protected areas, which were more effective at mitigating quarrying impacts than climate change. We highlight the need for conservation-explicit assessments and a mechanistic understanding of species’ conservation needs, such as quantitatively evaluating species vulnerability to threats, to support efficient conservation strategies. We call for conservation initiatives with specific objectives to include overlooked species in protected areas and adjust the conservation objectives to address specific threats.